Novel Protein Mg2046 Regulates Magnetosome Synthesis in Magnetospirillum gryphiswaldense MSR-1 by Modulating a Proper Redox Status - Wang, Xu; Zheng, Haolan; Wang, Qing; Jiang, Wei; Wen, Ying; Tian, Jiesheng; Sun, Jianbo; Li, Ying; Li, Jilun (Frontiers in Microbiology, 2019)
Magnetotactic bacteria (MTB) are a large, polyphyletic group of aquatic microorganisms capable of absorbing large amounts of iron and synthesizing intercellular nano-scaled nanoparticles termed magnetosomes. In our previous transcriptomic studies, we discovered that a novel gene (MGMSRv2_2046, termed as mg2046) in Magnetospirillum gryphiswaldense strain MSR-1 was significantly up-regulated during the period of magnetosome synthesis. In the present study, we constructed a MSR-1 mutant strain with deletion of mg2046 (termed Δmg2046) in order to evaluate the role of this gene in cell physiological status and magnetosome formation process. In comparison with wild-type MSR-1, Δmg2046 showed similar cell growth, but much lower cell magnetic response, smaller number and size of magnetosomes, and reduced iron absorption ability. mg2046 deletion evidently disrupted iron uptake, and redox equilibrium, and strongly inhibited transcription of dissimilatory denitrification pathway genes. Our experimental findings, taken together with results of gene homology analysis, indicate that Mg2046 acts as a positive regulator in MSR-1 under microaerobic conditions, responding to hypoxia signals and participating in regulation of oxygen metabolism, in part as a co-regulator of dissimilatory denitrification pathway with oxygen sensor MgFnr (MGMSRv2_2946, termed as Mg2946). Mg2046 is clearly involved in coupled regulation of cellular oxygen, iron and nitrogen metabolism under micro-aerobic or anaerobic conditions. Our findings help explain how MSR-1 cells initiate dissimilatory denitrification pathway and overcome energy deficiency under microaerobic conditions, and have broader implications regarding bacterial survival and energy metabolism strategies under hypoxia.